Police and procedural justice: perceptions of young people with mental illness - Morgan, Matthew M. (Policing and society, 2023)
Young people with mental illness are significantly more likely to encounter the police than their counterparts who do not identify as having a mental illness. Yet little is known regarding how this cohort perceives the police and whether they believe the police to be a fair, trustworthy, and legitimate service. Research suggests that young people and other vulnerable groups (such as adults with mental illness) value procedural justice policing as a technique for nurturing fair and trustworthy policing, which in turn, increases satisfaction with police interactions and willingness to cooperate with police. This study uses procedural justice as a lens for analysing the perceptions of young people with mental illnesses regarding the police. Drawing upon survey data from a sample of 3147 Australian participants aged between 14 and 25 years old – a third of which identified as having a mental health condition – results demonstrate that young people with a mental illness offered significantly lower perceptions of the police in relation to procedural justice. Young people identifying as not heterosexual or as trans* or gender diverse, and those who report that they are not seen as Australian, also offered significantly lower perceptions of police procedural justice. A theoretical explanation is offered for why these marginalised young groups perceive the police to be procedurally unjust. Tactics for how the police may nurture more trusting and supporting relationships with young people in general are also discussed.